2017
DOI: 10.1016/j.worlddev.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Poverty Decomposition Analysis: An Application to the Philippines

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(22 reference statements)
0
14
0
1
Order By: Relevance
“…Furthermore, with an exception of the Shapley decomposition, none of these decompositions satisfy the time-reversion consistency. In other words, the contribution of each component for the change in poverty from time t 0 to time t 1 is not the same as that component for the change from time t 1 to time t 0 with the opposite sign as pointed out by Fujii (2014).…”
Section: Review Of Related Literaturementioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, with an exception of the Shapley decomposition, none of these decompositions satisfy the time-reversion consistency. In other words, the contribution of each component for the change in poverty from time t 0 to time t 1 is not the same as that component for the change from time t 1 to time t 0 with the opposite sign as pointed out by Fujii (2014).…”
Section: Review Of Related Literaturementioning
confidence: 94%
“…To address these issues, Fujii (2014) proposed a dynamic poverty decomposition method based on integration, thereby effectively internalizing the reference period. He then demonstrated that his decomposition method can be extended to include additional components such as within-region inequality and between-region inequality components, which was not possible or practical before.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Context is a critical aspect of socially sensitive research involving vulnerable people, such as SE beneficiaries. Given that the significance of context wherein such factors as demography (Cudia, 2015), culture (Rivera, 2015), ethnicity, geographical location (Fujii, 2017), education, occupation, household size and risk of exposure to natural calamities impact an individual's experience of poverty (Bayudan-Dacuycuy and Lim, 2014), each participant was a case that represented an instance of beneficiary engagement and a unique life context (Eisenhardt, 2002). In my ethics application, I proposed to interview participants in communities engaged with various social enterprises.…”
Section: Social Entrepreneurship Research In the Developing Worldmentioning
confidence: 99%
“…Some scholars focused on the objects of relative poverty. In the identification of poor families, the United Nations Development Programme (UNDP) (Drewnowski and Specter 2004) treated per capita income, life expectancy, and literacy rate as effective indices of poor families (Duckett 1998;Fujii 2017;Gao and Zhai 2012;Gao et al 2011;Gazeley and Verdon 2014;Ge et al 2017). In the identification of poor areas, Alkire et al (Gao and Zhai 2012) delegated the power of poverty identification to village, township, and county levels and designed local approaches that identify relatively poor people according to local conditions.…”
Section: Introductionmentioning
confidence: 99%